2009
DOI: 10.1002/crat.200800541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of axial vibration on Bi12SiO20 crystal growth by vertical Bridgman technique

Abstract: Bi 12 SiO 20 single crystals have been grown successfully by vertical Bridgman technique. During the crystal growth process, different axial vibration amplitudes of 50 µm, 70 µm and 100 µm were applied with the same vibration frequency of 50 Hz. The effect of different axial vibration amplitudes on quality of the as-grown Bi 12 SiO 20 single crystals was discussed. The crystals have been characterized by X-ray rocking curve optical and absorption spectrum. The experimental results reveal that the axial vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Several papers discuss low-frequency vibration axially applied to the ampoule in vertical Bridgman growth [62,97,120,121]. No notable effect of vibration on microstructure, compositional profile, interface shape, etc.…”
Section: Application Of Avc In Crystal Growth Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several papers discuss low-frequency vibration axially applied to the ampoule in vertical Bridgman growth [62,97,120,121]. No notable effect of vibration on microstructure, compositional profile, interface shape, etc.…”
Section: Application Of Avc In Crystal Growth Methodsmentioning
confidence: 99%
“…No notable effect of vibration on microstructure, compositional profile, interface shape, etc. Feigelson and Borshchevsky [120], who grew CdTe crystals, and Zhang et al [97], who studied the growth of Bi 12 SiO 20 , have shown that low-frequency axial vibration applied to the growth ampoule could produce a perceptible effect. Feigelson and Borshchevsky [120], who grew CdTe crystals, and Zhang et al [97], who studied the growth of Bi 12 SiO 20 , have shown that low-frequency axial vibration applied to the growth ampoule could produce a perceptible effect.…”
Section: Application Of Avc In Crystal Growth Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Steady forced flows are obtained on the free surface of the liquid phase driven by pure axial vibration. Based on this hinting, axial vibration is introduced into the Bi 12 SiO 20 crystal growth in our laboratory (Y. Zhang et al, 2008(Y. Zhang et al, , 2009, in order to suppress the unsteady thermocapillary or buoyancy convections. Some results are described in the following.…”
Section: Improvement Of Crystallographic Perfection In Bi 12 Sio 20 Cmentioning
confidence: 99%